Complex dynamics through fuzzy chains. - Bucolo, M.
This paper gives a new contribution to characterize a class of complex systems build as arrays of coupled fuzzy logic based chaotic oscillators and investigates their dynamical features. Different spatio-temporal dynamics have been reproduced using interconnected fuzzy chaotic cells in order to study the effects, due to the variation of some parameters and network topologies, in the collective behavior and to highlight the synchronization capability of the complex fuzzy systems under consideration. The synchronization characteristics have been focused by defining a behavioral index.
Keywords: Chaotic oscillators; Complex system; Fuzzy chains; Fuzzy chaotic cells; Fuzzy logic; Fuzzy systems; Network topology; Spatio temporal dynamics; Synchronization